In search for a foundation for African philosophy - Stella Bassey Esirah (PREDESTINASI, 2021)
This article is a response to the various proposals for the Africanization of the philosophy curriculum in African schools. I am of the belief that Africa is not yet ready for the project of Africanizing the philosophy curriculum. This is, due to the dearth in African philosophers and scanty educational materials that could truly be termed African philosophy. A solid foundation for African philosophy must first be built, before any attempt at Africanizing the curriculum will succeed.  What should occupy the minds now is the search for a veritable foundation to situate African philosophy. The research employs the philosophical methods of critical analysis, reflective argumentation and textual analysis to drive home its point.